Hypothermically Stored Amniotic Membrane for the Treatment of Cartilage Lesions: A Single-Arm Prospective Study with 2-Year Follow-Up. (January 2022) - Tabet, Samuel K.; Kimmerling, Kelly A.; Hale, Galen J.; Munson, Natalie R.; Mowry, Katie C.
Objective: The purpose of this study was to determine the safety and efficacy of hypothermically stored amniotic membrane (HSAM) for the treatment of cartilage lesions of the knee using imaging, patient-reported outcomes (PROs), second-look arthroscopy, and histology. Patients were treated with HSAM and followed for 2 years. Design: Subjects with focal chondral lesions of the femur (International Cartilage Repair Society grade 3-4) were enrolled in this single-arm prospective study. Standard of care imaging was completed. PROs, including the Knee Injury and Osteoarthritis Outcome Score (KOOS), Marx Activity Scale, and Visual Analog Scale (VAS), were collected at baseline and at 3, 6, 12, 18, and 24 months. Three subjects underwent an optional arthroscopy and biopsy of the repair at 24 months. Results: Ten subjects were enrolled and completed the study. At 24 months, KOOS Sports & Recreation improved 173.3% and Quality of Life improved 195.3% from baseline. Marx Activity Scale increased 266.8% from 12 to 24 months. VAS scores improved 84.8% and 81.0% from baseline to 24 months for average and maximum pain. Modified Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) scoring showed that 7 of 10 subjects had complete defect repair and filling by 24 months. Biopsy staining for collagen II revealed integration and remodeling of HSAM into a mix of hyaline-like cartilage and fibrocartilage matrix. Conclusion: This study provides evidence supporting the safety and efficacy of HSAM for treating symptomatic cartilage lesions. Subjects showed a high degree of defect fill and integration with the native cartilage and reported improvements in pain and function post-treatment. Results provide important original data for future clinical trials.